Marketing in a Web 2.0 world with a Web 1.0 mentality: the challenge of social web marketing in academic institutions. (16th November 2010) - Wetsch, Lyle R.; Pike, Kristen
The internet has changed the way people live, work and communicate in a very short period of time. It was not that long ago that e-mail was considered the 'new wave' of communication (Wilkes, 1990) and the possibility of near instantaneous communication resulted in previous communication technologies being referred to as 'snail mail' due to its antiquated pace. While e-mail was originally adopted by the young, technically savvy generations, now older generations have followed suit. This pattern is consistent with each new wave of technology that enters the market. Many companies are content to offer their static web pages out to the general public, but the emerging generations are being raised on a more interactive and dynamic Web 2.0 world. In order to market effectively to these emerging generations, businesses and managers are forced to evaluate and adopt emerging technologies at a greater pace. This paper addresses the challenges that academic institutions face when moving to a Web 2.0 marketing concept when legacy thinking (Web 1.0) still resides in the organisation.